Krisis Hak dan Peran Laki-laki: Sebuah Penciptaan Film Pendek Bergenre Drama Keluarga - Herdiansyah Dwi Saputra; Muhammad Ibrah Juniarto; Muh. Bahruddin; Sutikno . (MDP Student Conference, 2026)
The issue of the crisis of men's rights and roles in the family is a real social phenomenon and has an impact on psychological, emotional, and relational aspects in the household. This research aims to produce fictional short films that raise the crisis as well as represent the dynamics of masculinity, mental health, and shifting gender roles in the family. The approach used is qualitative, drawing on observations, interviews, literature reviews, and direct production practices. The results of the research are presented as a fictional short film titled Long Sad Task, which depicts domestic conflict and a male identity crisis when their economic role is disrupted. Through a realistic visual approach, minimal dialogue, and the use of gestures and silence as emotional language, this film can build audience empathy, open up space for reflection, and challenge social constructs that limit the role of men to economic aspects.